2009
DOI: 10.1029/2008ja013697
|View full text |Cite
|
Sign up to set email alerts
|

Transpolar voltage and polar cap flux during the substorm cycle and steady convection events

Abstract: [1] Transpolar voltages observed during traversals of the polar cap by the Defense Meteorological Satellite Program (DMSP) F-13 spacecraft during 2001 are analyzed using the expanding-contracting polar cap model of ionospheric convection. Each of the 10,216 passes is classified by its substorm phase or as a steady convection event (SCE) by inspection of the AE indices. For all phases, we detect a contribution to the transpolar voltage by reconnection in both the dayside magnetopause and in the crosstail curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(101 citation statements)
references
References 72 publications
(127 reference statements)
7
93
1
Order By: Relevance
“…Hence, we suggest that at least locally, the nightside reconnection rate may be higher in the recovery than in the expansion phase. This is in line with the studies by Milan et al (2007), Milan et al (2008) and Lockwood et al (2009).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hence, we suggest that at least locally, the nightside reconnection rate may be higher in the recovery than in the expansion phase. This is in line with the studies by Milan et al (2007), Milan et al (2008) and Lockwood et al (2009).…”
Section: Discussionsupporting
confidence: 79%
“…Geophys., 31, 1021-1034, 2013 www.ann-geophys.net/31/1021/2013/ mean value is larger than the typical duration of an expansion phase, so this suggests that reconnection may take place at a significant amount in the recovery phases. Recently, Lockwood et al (2009) have found that the nightside reconnection voltages maximise in the recovery phase. The MIRACLE magnetometers showed that during recovery phases of Substorms 2-4, the westward electrojets continued to be intense within the main oval, well separated from the PCB.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A significant increase (30-40 kV) in the CPCP-NH (173 kV) is observed at this time. We hypothesize that this enhancement is due to an active magnetotail source of polar cap convection (see also Provan et al, 2004;Lockwood et al, 2009;Kullen et al, 2010). (1995) and Ruohoniemi and Baker (1998) (see also Chisham et al (2007)).…”
Section: Global Uv Aurora: Image Datamentioning
confidence: 99%
“…The relative contributions to the cross-polar cap potential (CPCP) from the dayside (CPCP/day) and nightside (CPCP/night) sources during intervals of substorm activity have been studied in recent years, applying different observational techniques (Bristow et al, 2004;Lockwood et al, 2009;Kullen et al, 2010;Gordeev et al, 2011;Andalsvik et al, 2011Andalsvik et al, , 2012. Fox et al (1999), Grocott et al (2002) and Provan et al (2004) estimated the convection response to isolated substorms by continuous observations, applying a ground-based radar technique.…”
Section: Introductionmentioning
confidence: 99%